'From a mother to another': creative experiences of sharing used children's clothing. Issue 7 (4th May 2019) - Ritch, Elaine L.
ABSTRACT: This paper explores how consumers deliberate and incorporate concerns for sustainability in their consumption behaviours, through the lens of children's clothing provisioning. Frustrated by the limited acknowledgement for sustainable issues within the UK mass market fashion retail sector, the participants reveal engaging with social innovation exchange initiatives, including networks of used children's clothing. The research is informed by 28 professionally working mothers who navigate between meeting the social needs of themselves and their family with their growing knowledge for sustainability. The networks are symbolic of shared social values and building supportive communities that provided emotional and practical pathways for family provisioning. The research illustrates how societal discourse around sustainability is growing and how alternative market structures provide routes that appeal to consumers practically, socially and ideologically. Moreover, the research contributes to understanding opportunities that advance the sustainability agenda, for marketing, social innovation initiatives and progressing sustainable businesses.